Simultaneous Electrophysiology and Imaging Reveal Changes in Lipid Membrane Thickness and Tension upon Uptake of Amphiphilic Gold Nanoparticles - Mashali, Farzin (Langmuir : the ACS journal of surfaces and colloids, 2023)
Amphiphilic gold core nanoparticles (AmNPs) striped with hydrophilic 11-mercapto-1-undecanesulfonate (MUS) and hydrophobic 1-octanethiol (OT) ligands are promising candidates for drug carriers that passively and nondisruptively enter cells. Yet, how they interact with cellular membranes is still only partially understood. Herein, we use electrophysiology and imaging to carefully assess changes in droplet interface bilayer lipid membranes (DIBs) incurred by striped AmNPs added via microinjection. We find that AmNPs spontaneously reduce the steady-state specific capacitance and contact angle of phosphatidylcholine DIBs by amounts dependent on the final NP concentration. These reductions, which are greater for NPs with a higher % OT ligands and membranes containing unsaturated lipids but negligible for MUS-only-coated NPs, reveal that AmNPs passively embed in the interior of the bilayer where they increase membrane thickness and lateral tension through disruption of lipid packing. These results demonstrate the enhanced evaluation of nano-bio interactions possible via electrophysiology and imaging of DIBs